PROGRESSIVE WAY OF THINKING ABOUT CONTEMPORARY EDUCATION - PERSONAL DISCUSSIONS - Prauzner, Tomasz (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The article presents personal reflections related to the adaptation of education in terms of current social challenges. Selected teaching postulates will be presented in relation to the current experiences and needs of the education system in the period of pandemic restrictions. The questions included are intended to make the reader reflect and public debate on the innovative changes that await contemporary didactics. In addition, the article will present the elements of own research related to the observation of cognitive activity using QEEG electroencephalographic studies. The analysis of cognitive activity is a key element in the assessment of didactic effectiveness. Due to the wide scope of scientific research, only selected sources of the author's publications will be indicated, in which the topic has been presented in detail.